2006
DOI: 10.1111/j.1467-9396.2006.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of EMU on Tourism*

Abstract: This paper estimates the effect of the euro on intra-EMU tourist flows by using a panel dataset of 20 OECD countries over the period 1995-2002. The results reveal that the euro has increased tourism, with an effect of around 6.5%. This is a noticeable impact given the early stage of the EMU analyzed. The robustness checks show that the evidence of a positive impact is quite widespread across EMU destination countries. Copyright � 2006 The Authors; Journal compilation � 2007 Blackwell Publishing Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
63
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 22 publications
(24 reference statements)
8
63
1
1
Order By: Relevance
“…Both studies concluded that the existence of a common currency had a moderate effect on tourist arrivals. Gil‐Pareja et al. (2007) reported an impact of 6.5 per cent in the case of EU economic and monetary union, whereas Santana et al.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Both studies concluded that the existence of a common currency had a moderate effect on tourist arrivals. Gil‐Pareja et al. (2007) reported an impact of 6.5 per cent in the case of EU economic and monetary union, whereas Santana et al.…”
Section: Introductionmentioning
confidence: 95%
“…Although the effect of a common currency on international trade has been extensively studied, international tourism has failed to attract the attention of international economists in this respect. To date, and to the best of our knowledge, only two studies have explicitly taken into account the influence of a common currency on tourism (Gil‐Pareja et al, 2007; Santana et al, 2010). Both studies concluded that the existence of a common currency had a moderate effect on tourist arrivals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the large scale of operations leads to a higher number of lines connecting ports and, thus, increasing the competitive pressure in the transport market and, as a result, lowering the cost of transport services. 9 These models have been applied to trade Metcalf, 2005, 2006;Papazoglou et al, 2006;Armstrong 2007;Spies and Marques, 2009;Marques, 2011), migration (Gil-Pareja et al 2006;Marques, 2010), FDI (Head and Ries 2008), and tourism (Eilat and Einav, 2004;Gil-Pareja et al, 2007;Santana et al, 2010;Fourie and Santana 2013;Rosselló and Santana-Gallego 2014). Moreover, this specification has also been used both in the international and regional context (see, for the case of Spain, Sansó et al, 1990, Sanz, 2000and Gil-Pareja et al, 2005 variable cost, which depends on distance, and a specific trade cost, which exists only for some trade partners (in our case, islands).…”
Section: Introductionmentioning
confidence: 99%